155k views
4 votes
Find the sum of each of the following polynomials.

a)
x^3+5x^2+2, 3x^2-4x+7
b)
2x + 5x^3-2x^2+7, 9+4x-5x^2-2x^3
c)
5x^3+2x^2+4, 2x^2+7x-5, 7-5x^2 +3x-4x^3
d)
2x^4-3x^2+4x^3-5, 9x^2-7x^3-2x^4, 7-x+3x^4

1 Answer

2 votes

Answer:


(a)\ Sum = x^3+8x^2-4x+9


(b)\ Sum =3x^3-7x^2+6x +16


(c)\ Sum = x^3-x^2+10x+6


(d)\ Sum = 3x^4 -3x^3+ 6x^2-x+2

Explanation:

Required

Sum of the polynomials


(a)\ x^3+5x^2+2, 3x^2-4x+7


Sum = x^3+5x^2+2+3x^2-4x+7

Collect like terms


Sum = x^3+5x^2+3x^2-4x+2+7


Sum = x^3+8x^2-4x+9


(b)\ 2x + 5x^3-2x^2+7, 9+4x-5x^2-2x^3


Sum =2x + 5x^3-2x^2+7+ 9+4x-5x^2-2x^3

Collect like terms


Sum =5x^3-2x^3-2x^2-5x^2+4x+2x +7+ 9


Sum =3x^3-7x^2+6x +16


(c)\ 5x^3+2x^2+4, 2x^2+7x-5, 7-5x^2 +3x-4x^3


Sum = 5x^3+2x^2+4+ 2x^2+7x-5+ 7-5x^2 +3x-4x^3

Collect like terms


Sum = 5x^3-4x^3+2x^2+ 2x^2-5x^2+7x+3x-5+ 7 +4


Sum = x^3-x^2+10x+6


(d)\ 2x^4-3x^2+4x^3-5, 9x^2-7x^3-2x^4, 7-x+3x^4


Sum = 2x^4-3x^2+4x^3-5+ 9x^2-7x^3-2x^4+ 7-x+3x^4

Collect like terms


Sum = 2x^4-2x^4+3x^4 +4x^3 -7x^3-3x^2+ 9x^2-x-5+ 7


Sum = 3x^4 -3x^3+ 6x^2-x+2

User Conan
by
6.4k points